Impact-Induced Delamination Detection of Composites Based on Laser Ultrasonic Zero-Lag Cross-Correlation Imaging - Yun-Kyu An (Advances in Materials Science and Engineering)
This paper presents impact-induced delamination visualization by zero-lag cross-correlation (ZLCC) imaging computed using fully noncontact laser scanned ultrasonic wavefields. The proposed technique enables instantaneous visualizing of invisible delamination of composite materials without any sensor installation. Moreover, it provides robust damage diagnosis without comparing with baseline data obtained from the undamaged condition of a target structure, making it possible to minimize false alarms. First, the existence of internal delamination-induced standing waves is proven by employing a finite element analysis. Then, how ZLCC can physically isolate and visualize only the standing wave feature from the measured ultrasonic wavefields is shown. To experimentally validate the proposed technique, a fully noncontact laser ultrasonic imaging system is introduced, and the internal delamination is visualized by laser scanning in a graphite fiber composite plate. The experimental results reveal that hidden delamination is successfully and automatically visualized and quantified without any users’ intervention.